Medicinal plants : chemistry, pharmacology, and therapeutic applications - Swamy, Mallappa Kumara; Patra, Jayanta Kumar; Rudramurthy, Gudepalya Renukaiah (CRC Press / Taylor & Francis Group, 2019)
This book details several important medicinal plants, their occurrence, plant compounds and their chemical structures, and pharmacological properties against various human diseases. It also gives information on isolation and structural elucidation of phytocompounds, bio-assays, metabolomic studies, and therapeutical applications of plant compounds.